The Impact of ACEs on Individuals and Nurses - Vinall, Maria (MD Conference Express, 2015)
The Adverse Childhood Experiences Study is a long-term research effort started in the 1990s to understand the impact of childhood trauma on health, social, and economic outcomes. The study is a collaborative effort between the US Centers for Disease Control and Prevention (CDC) in Atlanta, Georgia, and Kaiser Permanente's Health Appraisal Clinic in San Diego, California. Three presenters reviewed how the too-often invisible nature of childhood trauma can change a child's epigenome early in life, leading to physical and mental health problems throughout the child's lifetime.